1997
DOI: 10.1002/bjs.1800840827
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of postoperative radiotherapy and short-term time-scheduled 5-fluorouracil against surgery alone in the treatment of Dukes B and C rectal cancer

Abstract: The 1-month postoperative combination regimen improved treatment results in patients with Dukes B and C rectal cancer, in terms of local recurrence rate, recurrence-free survival and overall survival, without serious side-effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
57
3
13

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(76 citation statements)
references
References 22 publications
3
57
3
13
Order By: Relevance
“…The acute and late toxicity on our series correlates with the findings from other series using appropriate radiotherapy techniques [28,36,49,51].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The acute and late toxicity on our series correlates with the findings from other series using appropriate radiotherapy techniques [28,36,49,51].…”
Section: Discussionsupporting
confidence: 74%
“…The overall 5-year survival (63%) and disease-free survival (53%) for the 68 patients treated with radiochemotherapy in our series are slightly lower than that reported from randomized trials recently [36,49,51]. The previous mentioned possible negative patient selection in our series, due to the nonstandardized criteria for adjuvant treatment during this period, might be a reason for this.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…The prognosis of LARC has been improved considerably in recent years with the introduction of total mesorectal excision, 9 adjuvant therapy, 13,14 and the addition of multimodal neoadjuvant treatment. Some studies have demonstrated that preoperative radiation with or without chemotherapy in LARC improved local control [15][16][17] and survival rate 15,18 compared with surgery alone.…”
Section: Discussionmentioning
confidence: 99%